Redes sociales y contenidos periodísticos sin censura en la proyección informativa nacional - Aragundi Fernández, Alex Elías (2024)
The information that circulates through social networks can be considered a double-edged sword, taking into account the time of the pandemic, where hoaxes about the COVID-19 virus emerged. On the one hand, there were news broadcasts by qualified journalists with the knowledge and experience to transmit news, on the other hand, pseudo-journalists who lacked this knowledge. This is reflected between the publications of journalists from the digital media outlet Instagram, Última Hora Ecuador, and the Facebook and X publications of pseudo journalists, who are considered informal communicators, because they are creators of false material. This content doesn't just affect news consumers on the web, it also affects journalists who strive to keep the truth in their news.